Kecemasan pada Penderita Penyakit Ginjal Kronik yang Menjalani Hemodialisis di RS Universitas Kristen Indonesia - Luana NA; Sahala Panggabean; Joyce VM Lengkong; Ika Christine (MEDIA MEDIKA INDONESIANA, 2012)
Anxiety in chronic renal failure patients underwent hemodialysis at Christian University of Indonesia HospitalBackground: Anxiety is a pathological condition, characterized by fear and somatic signs. Anxiety is also a response to unidentified, internal, vague threads and conflicts. One of the etiologies of anxiety is biological disorder, such as chronic renal failure (CRF) which needs hemodialysis. Hemodialysis patients experience anxiety, which probably due to its chronicity. The aim of this study is to identify the difference of frequency and period of hemodialysis in various level of anxiety in CRF patients underwent hemodialysis atChristian University of Indonesia Hospital.Methods: This is an observational study with cross-sectional design, conducted during October-December 2011. Anxiety level was measured using the Hamilton Rating Scale for Anxiety (HRSA). Kruskall Wallis test was used to analyze the difference of frequency and period of hemodialysis in three levels of anxiety (mild, moderate, and severe).Results: Twenty eight (51.9%) men and 26 (48.1%) women with CRF who underwent hemodialysis at Christian University of Indonesia Hospital were included in this research. There were 42 (77.78%) among them who experienced anxiety. Patients with the longest mean of period and frequency of hemodialysis experienced mild anxiety, whereas patients with the shortest mean of period and frequency of hemodialysis experience moderate anxiety. There are significant differences found between period and frequency of hemodialysis and levels of anxiety (p=0.002 and p=0.003, respectively).Conclusion: There are significant differences found between period and frequency of hemodialysis and levels of anxiety.Keywords: Hemodialysis, anxiety, HARS ABSTRAKLatar belakang: Cemas (ansietas) adalah suatu keadaan patologik yang ditandai oleh perasaan ketakutan diikuti dan disertai tanda somatik. Kecemasan juga merupakan respon terhadap suatu ancaman yang sumbernya tidak diketahui, internal, samar-samar, atau konfliktual. Kecemasan salah satunya disebabkan oleh gangguan biologik, seperti penyakit ginjal kronik (PGK) yang membutuhkan hemodialisis. Penderita hemodialisis mengalami kecemasan, salah satunya dapat diakibatkan oleh kronisitas penyakit. Penelitian ini bertujuan untuk mengetahui perbedaan frekuensi dan periode menjalani hemodialisis pada berbagai derajat kecemasan pada penderita penyakit ginjal kronik yang menjalani hemodialisis di RS Universitas Kristen Indonesia.Metode: Penelitian ini adalah penelitian observasional dengan rancangan cross-sectional, dilakukan selama bulan Oktober- November 2011. Pengukuran derajat cemas menggunakan instrument Hamilton Rating Scale for Anxiety (HRSA). Dilakukan analisis uji beda Kruskall Wallis untuk menganalisis perbedaan frekuensi dan periode hemodialisis pada tiga derajat kecemasan (ringan, sedang, dan berat).Hasil: Dua puluh delapan (51,9%) laki-laki dan 26 (48,1%) perempuan penderita PGK yang menjalani hemodialisis di Universitas Kristen Indonesia ikut serta dalam penelitian ini. Terdapat 42 (77,78%) di antaranya yang mengalami kecemasan. Penderita dengan rerata periode dan frekuensi hemodialisis terpanjang mengalami kecemasan ringan, sedangkan penderita rerata periode dan frekuensi hemodialisis terpendek mengalami kecemasan sedang. Terdapat perbedaan yang bermakna antara frekuensi dan periodehemodialisis dan derajat kecemasan pada penderita hemodialisis (p=0,002 dan p=0,003, secara berurutan).Simpulan: Terdapat perbedaan yang bermakna antara frekuensi dan periode hemodialisis dan derajat kecemasan pada penderita hemodialisis.